Rethinking Collective Burial in Mediterranean Caves: Middle Bronze Age Grotta Regina Margherita, Central Italy. (18th August 2021) - Skeates, Robin; Beckett, Jessica; Mancini, Daniela; Cavazzuti, Claudio; Silvestri, Letizia; Hamilton, W. Derek; Sayle, Kerry L.; Crowder, Kayla D.; Rolfo, Mario; Angle, Micaela
ABSTRACT: Drawing on the results of new multi-method research in Grotta Regina Margherita—the largest known Middle Bronze Age mortuary cave in west-central Italy (ca. 1650–1450 b.c. )—this article helps to replace the generic idea of "collective burial" with a more precise understanding of how the bodies of the deceased were transformed into potent social, symbolic, and sensuous resources housed in caves. It contextualizes this process within a nuanced understanding of settlement and subsistence practices, in which relatively short-lived and small-scale agricultural communities extended inland to the edge of the Apennine Mountains, ritually demarcating mortuary assemblages in caves in the process.